Fatigue of weld ends under combined in- and out-of-phase multiaxial loading (Fracture and Structural Integrity, 2016)
Weld start and end points are fatigue failure sensitive locations. Their fatigue behaviour especially in thin sheet structures under multiaxial load conditions is not sufficiently explored so far. Therefore, a research project was initiated to increase the knowledge concerning this topic, which is of special interest in the automotive industry. In the present study, fatigue tests on welded joints were conducted. In the numerical part of the study, notch stresses were calculated with an idealised weld end model. A numerical method which combines the geometrical and statistical size effect to an integrated approach was used, in order to consider the size effects.
Keywords: Weld ends; Fatigue; Notch stress; Size effect; Multiaxial